The Application of Social Media in Early Childhood Mental Development - Ulfadhilah, Khairunnisa; Nurkhafifah, Salsabila Dwi (Muttaqien Publishing, Pusat Penelitian dan Pengabdian kepada Masyarakat STAI DR.KH.EZ.Muttaqien Purwakarta, 2025)
Social media has a bad impact on young children if it is not supervised by parents. Viewings on social media such as TikTok, YouTube shorts and Instagram reels are not intended for children, so young children should not be allowed to access them. If young children access social media without being accompanied by parents or adults, it will have an impact on the development of the child's soul, character and habit of children continuing to watch shows on social media. The development of a child's soul is a good example for children because it is in the golden age stage where stimulation is good. In social media the regulations are not yet strict because many are not suitable for viewing by children, videos circulating on social media are simply uploaded without thinking about the negative impacts if accessed by children. The role of father and mother is very important for children who access the internet and social media, so they need to be supervised, limited to viewing appropriate to the child's age, and provided understanding and explanation when children watch social media by parents because at an early age, the critical stage for children is always asking about anything. Literature was obtained from Google Scholar, Mendeley, and references by the author. The publication documents used as references are based on the year 2020-2023.